Saponins From Paris forrestii (Takht.) H. Li Display Potent Activity Against Acute Myeloid Leukemia by Suppressing the RNF6/AKT/mTOR Signaling Pathway - Lu, Qin; He, Yuanming; Wang, Yuehu; Gao, Li; Zheng, Yunjing; Zhang, Zubin; Cao, Biyin; Wang, Qi; Mao, Xinliang; Hu, Shaoyan (Frontiers in Pharmacology, 2018)
Saponins are amphipathic glycosides found in traditional Chinese medicines. In the present study, we isolated a panel of saponins from Paris forrestii (Takht.) H. Li, a unique plant found in Tibet and Yunnan provinces, China. By examining their activities in suppressing acute myeloid leukemia (AML) cell proliferation, total saponins from Paris forrestii (TSPf) displayed more potent activity than individual ones. TSPf induced more than 40% AML cell apoptosis and decreased the viability of all leukemia cell lines. TSPf-induced apoptosis was confirmed by both Annexin V staining and caspase-3 activation. In line with these findings, TSPf downregulated pro-survival proteins Mcl-1, Bcl-xL and Bcl-2 but upregulated the expression of tumor suppressor proteins p53, p27, Bax and Beclin 1. The AKT/mTOR signaling pathway is frequently overactivated in various AML cells, and TSPf was found to suppress the activation of both AKT and mTOR, but had no effects on their total protein expression. This was further confirmed by the inactivation of 4EBP-1 and p70S6K, two typical downstream signal molecules in the AKT/mTOR pathway. Moreover, TSPf-inactivated AKT/mTOR signaling was found to be associated with downregulated RNF6, a recently identified oncogene in AML. RNF6 activated AKT/mTOR, and consistently, knockdown of RNF6 led to inactivation of the AKT/mTOR pathway. Furthermore, TSPf suppressed the growth of AML xenografts in nude mice models. Oral administration of TSPf almost fully suppressed tumor growth without gross toxicity. Consistent with the findings in cultured cell lines, TSPf also downregulated RNF6 expression along with inactivated AKT/mTOR signaling in tumor tissues. This study thus demonstrated that TSPf displays potent anti-AML activity by suppressing the RNF6/AKT/mTOR pathway. Given its low toxicity, TSPf could be developed for the treatment of AML.